2019
DOI: 10.21873/anticanres.13688
|View full text |Cite
|
Sign up to set email alerts
|

Previous Immune Checkpoint Inhibitor Treatment to Increase the Efficacy of Docetaxel and Ramucirumab Combination Chemotherapy

Abstract: Background/Aim: For immune checkpoint inhibitor (ICI)-pretreated patients, docetaxel and ramucirumab (DOC+RAM) combination therapy may be more effective compared to patients not receiving ICI treatment. Patients and Methods: From June 2013 to July 2018, 39 patients with advanced/recurrent non-small cell lung cancer underwent DOC+RAM therapy. We analyzed the efficacy and safety of DOC+RAM therapy based on the presence (pre-ICI+) or absence (pre-ICI-) of ICI pretreatment history. Results: Of the 39 patients trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
85
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(95 citation statements)
references
References 12 publications
9
85
1
Order By: Relevance
“… 16 While this registration trial showed a median PFS of 4.5 months for this combination, our cohort showed a median PFS of 6.8 months and a DOR of 10.2 months. A similar observation has previously been demonstrated in a small retrospective analysis by Harada et al 18 This group reported a median PFS of 5.7 months with a sequence of ICI followed by R + D in contrast to 2.3 months with R + D followed by ICI ( P = 0.020). Our data are also in line with another small study from Japan reporting a median PFS of 5.9 months using R + D after ICI.…”
Section: Discussionsupporting
confidence: 86%
“… 16 While this registration trial showed a median PFS of 4.5 months for this combination, our cohort showed a median PFS of 6.8 months and a DOR of 10.2 months. A similar observation has previously been demonstrated in a small retrospective analysis by Harada et al 18 This group reported a median PFS of 5.7 months with a sequence of ICI followed by R + D in contrast to 2.3 months with R + D followed by ICI ( P = 0.020). Our data are also in line with another small study from Japan reporting a median PFS of 5.9 months using R + D after ICI.…”
Section: Discussionsupporting
confidence: 86%
“…Grade 1 or 2 diarrhoea or stomatitis were also more frequent in the anti-PD-1-exposed group than the anti-PD-1-naïve group among patients with taxanes plus RAM, consistent with the safety profiles of docetaxel plus RAM before and after PD-1 therapy in NSCLC, or in a phase II study of nivolumab combined with PTX plus RAM. 19 30 Further analysis with a large sample size as well as pretreatment and post-treatment biopsies is thus essential to clarify the immunological effect of taxanes plus RAM after PD-1 therapy on such toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…The other mechanism is the combination of cytotoxic and antiangiogenic agents resulting in an intensified ICI treatment effect . However, Harada et al reported that docetaxel and ramucirumab chemotherapy after ICI treatment induced ILD in three out of 18 patients . Although CT findings showed similar diffuse GGO in our three patients, we could not obtain pathological specimens and the aetiology remains unclear.…”
Section: Discussionmentioning
confidence: 56%
“…Although the mechanisms underlying the association are unknown, nivolumab has been thought to successfully activate the host immune system. On the other hand, chemotherapy with docetaxel and ramucirumab after ICI treatment was reported to show high efficacy compared to that noted in cases without the previous use of ICI treatment . It has been suggested that the high efficacy of docetaxel and ramucirumab after ICI treatment is attributable to the following two mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation